2024
DOI: 10.1021/acsapm.3c02299
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Polymer-Layered Silicate Hybrids for Anticorrosion

Chalunda Tirayaphanitchkul,
Krisada Auepattana-Aumrung,
Daniel Crespy
et al.

Abstract: Two-dimensional materials have been introduced in polymer coatings to increase the lifetime of metallic materials by providing barrier properties against corrosive species. Corrosion inhibitors can be inserted into a 2D filler to mitigate the corrosion of metallic materials caused by corrosive species. Current drawbacks of this approach include a poorly controlled release of the inhibitor and the incompatibility of the filler and polymer. To achieve long-term anticorrosion performance, a layered silicate (octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…1 μm, while the internal and external diameters are between 10–15 and 50–80 nm, respectively. ,, It is important to note that halloysite can be easily dispersed in water without the need for time-consuming exfoliation procedures required for other platy clays . Due to their attractive colloidal properties and versatile surface, , HNTs can be used in drug delivery, catalysis, remediation, nanocontainers for anticorrosive compounds, , and conservation of cultural heritage. , It is reported that halloysite modified by anionic surfactants produce inorganic micelles with solubilizing capacity toward hydrophobic molecules. , The filling of polymeric matrix with halloysite is proper to fabricate composite materials with excellent mechanical performances, vapor barrier properties, high thermal stability, and flame retardant characteristics. , Halloysite possesses peculiar interface properties since its outer and inner surfaces are oppositely charged within a large pH interval. Specifically, the surface cavity is positive, and the shell is negative for pH larger than ca.…”
Section: Introductionmentioning
confidence: 99%
“…1 μm, while the internal and external diameters are between 10–15 and 50–80 nm, respectively. ,, It is important to note that halloysite can be easily dispersed in water without the need for time-consuming exfoliation procedures required for other platy clays . Due to their attractive colloidal properties and versatile surface, , HNTs can be used in drug delivery, catalysis, remediation, nanocontainers for anticorrosive compounds, , and conservation of cultural heritage. , It is reported that halloysite modified by anionic surfactants produce inorganic micelles with solubilizing capacity toward hydrophobic molecules. , The filling of polymeric matrix with halloysite is proper to fabricate composite materials with excellent mechanical performances, vapor barrier properties, high thermal stability, and flame retardant characteristics. , Halloysite possesses peculiar interface properties since its outer and inner surfaces are oppositely charged within a large pH interval. Specifically, the surface cavity is positive, and the shell is negative for pH larger than ca.…”
Section: Introductionmentioning
confidence: 99%